PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM SEKOLAH DAN MOTIVASI BERPRESTASI TERHADAP KOMITMEN GURU SMK NEGERI SEKABUPATEN OKU TIMUR - Novitasari, Novitasari; Subarjono, Subarjono; Akman, Yuli; Solikhan, Solikhan (Jurnal Signaling, 2024)
The purpose of this study was to determine and analyze the leadership principal, School Climate And Achievement Motivation To Commitment Of Teacher SMK N east Oku Timur Provinsi Sumatera Selatan. This study was a quantitative descriptive research, the population in this study are all public school teachers in the SMK Negeri east Oku Timur Provinsi Sumatera Selatan 330 teacher, with a sample of 101 teachers. Data was collected by questionnaire. Analysis of data using path analysis (path analysis) and hypothesis testing. The results of this study indicated that Leadership Principal significantly influence teachers' Commitment, School Climate significant effect on teacher Commitment, achievement motivation significant effect on the School Climate of teachers. Leadership Principal, School Climate, achievement motivation jointly significant effect on Commitment Of Teacher.